An Antibiotic Nanobomb Constructed from pH‐Responsive Chemical Bonds in Metal‐Phenolic Network Nanoparticles for Biofilm Eradication and Corneal Ulcer Healing - Qiang Gao; Xiaoying Chu; Jie Yang; Yishun Guo; Hanwen Guo; Siyuan Qian; Ying‐Wei Yang; Bailiang Wang (Advanced Science, 2024)
Abstract In the treatment of refractory corneal ulcers caused by Pseudomonas aeruginosa, antibacterial drugs delivery faces the drawbacks of low permeability and short ocular surface retention time. Hence, novel positively‐charged modular nanoparticles (NPs) are developed to load tobramycin (TOB) through a one‐step self‐assembly method based on metal‐phenolic network and Schiff base reaction using 3,4,5‐trihydroxybenzaldehyde (THBA), ε‐poly‐ʟ‐lysine (EPL), and Cu2+ as matrix components. In vitro antibacterial test demonstrates that THBA‐Cu‐TOB NPs exhibit efficient instantaneous sterilization owing to the rapid pH responsiveness to bacterial infections. Notably, only 2.6 µg mL−1 TOP is needed to eradicate P. aeruginosa biofilm in the nano‐formed THBA‐Cu‐TOB owing to the greatly enhanced penetration, which is only 1.6% the concentration of free TOB (160 µg mL−1). In animal experiments, THBA‐Cu‐TOB NPs show significant advantages in ocular surface retention, corneal permeability, rapid sterilization, and inflammation elimination. Based on molecular biology analysis, the toll‐like receptor 4 and nuclear factor kappa B signaling pathways are greatly downregulated as well as the reduction of inflammatory cytokines secretions. Such a simple and modular strategy in constructing nano‐drug delivery platform offers a new idea for toxicity reduction, physiological barrier penetration, and intelligent drug delivery.